PENGARUH KOMPETENSI INDIVIDU, INSENTIF, DAN MOTIVASI INTRINSIK TERHADAP KINERJA PEGAWAI PERUM BULOG DIVRE KAMPAR - Setiawan, Nanda; -, Marnis; Marpaung, Rio (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was aims in Perum Bulog Divre Kampar. The purpose of this study was to determine 1) To determine the effect of individual competence, incentives and intrinsic motivation simultaneously on the performance of Employees Perum Bulog Divre Kampar. 2) To determine the effect of individual competence, incentives and intrinsic motivation partially on employee performance Perum Bulog Divre Kampar. 3) To determine which variables are the most significant influence on employee performance of Perum Bulog Divre Kampar. The number of samples in this study were 56 employees Perum Bulog Divre Kampar.The results of this study resulted in 1) There is the influence of individual competencies, incentives and intrinsic motivation simultaneously on the performance of Employees Perum Bulog Divre Kampar. 2) influences of individual competencies, incentives and intrinsic motivation partially on employee performance Perum Bulog Divre Kampar.3) individual competence is the most significant variable effect on employee performance Perum Bulog Divre Kampar.Keywords: Individuals Competence, Incentives, Intrinsic Motivation, Performance.